2018
DOI: 10.1016/j.neubiorev.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of validity and utility of translational imaging in pain and analgesia: Utilizing functional imaging to enhance the process

Abstract: Assessing clinical pain and metrics related to function or quality of life predominantly relies on patient reported subjective measures. These outcome measures are generally not applicable to the preclinical setting where early signs pointing to analgesic value of a therapy are sought, thus introducing difficulties in animal to human translation in pain research. Evaluating brain function in patients and respective animal model(s) has the potential to characterize mechanisms associated with pain or pain-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 229 publications
0
11
0
Order By: Relevance
“…Second, the present approach might represent a step further towards a much sought-after brain-based marker of pain. 15,71 fMRI recordings have already shown that, in principle, it is possible to establish such a marker. 44,80 The present approach complements these fMRI approaches by using EEG recordings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the present approach might represent a step further towards a much sought-after brain-based marker of pain. 15,71 fMRI recordings have already shown that, in principle, it is possible to establish such a marker. 44,80 The present approach complements these fMRI approaches by using EEG recordings.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a brain-based marker of chronic pain could be immensely helpful for the diagnosis, prognosis, classification, prevention, and treatment of pain. 15,71 Accordingly, the feasibility, limitations, and perspectives of brain-based markers of pain are currently intensively discussed in the pain research community 15,50,64 and beyond. 43,56,84 Recent functional magnetic resonance imaging (fMRI) studies have made important first steps towards such a brain-based marker of experimental 80 and chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this phenomenon is specific for CRPS or applies to all kinds of hand immobilization is currently unknown. For more information about functional imaging in CRPS, we refer the reader to reviews that concentrate on this field of research 25,26 .…”
Section: Diagnostic Features and Biomarkersmentioning
confidence: 99%
“…The gap between animal and human studies is large (and growing), and models should increasingly use results and concepts from animal neuroscience to constrain and corroborate human predictive models. 140…”
Section: Discussionmentioning
confidence: 99%